Comparison of numerous delivery systems for the induction of cytotoxic T lymphocytes by immunization. - Allsopp, C; Plebanski, M; Gilbert, S; Sinden, R; Harris, S; Frankel, G; Dougan, G; Hioe, C; Nixon, D; Paoletti, E; Layton, G; Hill, A (1996)
A variety of vaccine delivery systems including peptides with various adjuvants, recombinant particles, live recombinant viruses and bacteria and plasmid DNA were tested for their ability to induce CD8+ cytotoxic T lymphocytes (CTL) against a well-defined epitope (amino acids 252-260) from the circumsporozoite (CS) protein of Plasmodium berghei. We compared routes of immunization that would be applicable for the administration of a malaria vaccine in humans. The majority of these vaccines did not induce high CTL responses in the spleens of immunized mice. However, both a yeast-derived Ty virus-like particle expressing the optimal nine-amino acid epitope SYIPSAEKI from the CS protein (CSP-VLP) and a lipid-tailed peptide of this same sequence induced high levels of the major histocompatibility complex (MHC) class I-restricted CTL with one and three subcutaneous immunizations, respectively. Moreover, these CTL were able to recognize naturally processed antigen expressed by a recombinant vaccinia virus. The levels of CTL induced by CSP-VLP could be augmented by co-immunization with certain cytokines. Target cells pulsed with CSP-VLP were recognized and lysed, showing that the particles were effectively processed and presented through MHC class I presentation pathway. The levels of CTL induced using CSP-VLP and lipopeptides are comparable to those observed after immunization with multiple doses of irradiated sporozoites.